Authority of organs of constitutional jurisdiction on issues of international agreements: the experience of foreign states and Ukraine - Kaminska, Nataliia (ScienceRise: Juridical Science, 2023)
In the conditions of Ukraine's implementation of the status of a candidate for EU accession, post-war reconstruction, the Constitutional Court of Ukraine, along with other authorities, is entrusted with the important mission of affirming and implementing universal human values and international standards. The purpose of the article is a comparative analysis of the powers of the organs of constitutional jurisdiction on issues of international treaties, for which the following tasks must be solved: - to find out the state of regulation of the powers of organs of constitutional jurisdiction relating to international treaties in the Constitution of Ukraine and the constitutions of foreign states; - to generalize the trends and regularities of the constitutional and legal provision of powers of these organs in this direction; - to determine prospective directions of improvement of the constitutional and legal regulation of the powers of the ССU in the conditions of European integration. The methodological toolkit of the research consists of general scientific and special legal methods (dialectical, comparative legal, logical, epistemological, axiological, formal-legal, structural-functional, hermeneutic, statistical, prognostic, etc.), systemic, pluralistic, complex approaches, appropriate methodological principles The constitutional and legal regulation of the powers of organs of constitutional jurisdiction is carried out in the constitutions, in most states there are special laws (constitutional or organic) on the constitutional court (council, tribunal, etc.), which regulate in detail the functions, powers of these organs and their members, the order of formation, procedures of activity etc. The main powers of these organs include, inter alia, consideration of issues of compliance of laws with ratified international treaties, provisions of other acts, issued by central state organs, with the constitution, ratified international treaties and laws (prior and subsequent constitutional control). The scope of competence of the organs of constitutional jurisdiction of foreign states and their effectiveness is much greater than that of the ССU, so it is advisable to modernize it. In particular, the experience of Slovakia and Poland is worth noting, especially in view of their accession to the EU, the expansion of the competence of constitutional jurisdiction organs and certain procedures of their activities, including constitutional control over international treaties